A Novel Hybrid Method for DAP: Differential Evolution with Variable Neighborhood Search - Thakur, Mamta; Sushma, Talluri; Vellanki, Nagaraju; Shareef, R. M. Mastan; Anusha, Peruri Venkata; Swarna, B; Peter, Geno (Malikussaleh University, Aceh, Indonesia, 2025)
This research investigates MOPFSP-SDST, an advanced and highly computational scheduling difficulty in real-world manufacturing systems. It examines how it correlates with multi-objective permutation flow shops. LS-MOVNS stands for